Envisioning research through a lens of play - Alex Moseley; Dawn Watkins (University of Huddersfield Press, 2022)
In this paper, two higher education researchers - one, an experienced play researcher and practitioner; the other an experienced Law researcher who has more recently engaged with the play literature - present their ideas concerning what happens, or what could happen when research is envisioned through a lens of play. They describe how, drawing on the literature and theories surrounding play and games, they worked together to identify features that resonated with them as being relevant to research. Through their discussion of seven resonators (the significance of play, play is voluntary, play challenges, the uncertainty of play, accepting failure, community building and working within constraints) they suggest a playful look at research might encourage a number of positive changes to research practice and impact. They conclude by inviting readers to critically examine their claims, and to test them out in the contexts of their own research environments.